GAMBARAN PERILAKU MEROKOK PADA PENDERITA DM TIPE II - Riga Opri Sandrelly; Darwin Karim; Sofiana Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Smoking behavior is a behavior that can cause some of health problems, one of them is increasing the risk of type II DM and also increasing the risk of complications in people with type II DM for those who is still smoking. This study aim to describe the smoking behavior in patients with type II diabetes in five Pekanbaru Health Centers with a descriptive research design and cross sectional approach. The sample of this study was 100 respondents taken based on inclusion criteria used the puprosive sampling technique. The measuring instrument used was a smoking behavior questionnaire and Fagerstrom questionnaire that has been tested its validity and reliability. The univariate analysis was conducted to know frequency distribution. The results showed from 100 respondents, 97 respondents (97%) with smoking >20 years, with 79 respondents (79%) in the light smoker category, patients with DM type II who smoke have the smoking behavior that is influenced by negative feelings by 49 respondents (49%), with the level of dependence on cigarettes being a low dependency of 69 respondents (69%). The result of this research was recommended to the patients of DM type II who are still smoking to quit smoking as preventive efforts against complication and also for the nurses to provide health education regarding the impact that occurs when the DM patient is still smoking. Keywords: Complications, DM type II, Smoking behavior